Electrical Signals in the Nervous System - Zeise-Ssa., M (Springer International Publishing, 2020)
Living systems are auto-organizing systems. To achieve this auto-organization, communication is necessary and signals must be generated. As any living organism displays and uses electricity based in diffusion potentials, varying those voltages, electrical signals may be created. The nervous system has developed in multicellular organisms that move actively. It generates fast electrical signals of a digital character in neurons to communicate over distances that exceed by far the dimension of the neuron’s cell body. Further, electrical signals of an analogous type are generated in “postsynaptic” parts of the contacts with other neurons. These “postsynaptic” signals are inhibitory or excitatory and are integrated forming the eventual output via the extended “axon” that communicates signals to other cells. This chapter briefly introduces the basic parameters of electricity and then explains how these electrical signals are produced. The crucial role of ionic channels and their mode of action are explained. Finally, the integration of electric signals in neurons and their energetic power source are discussed. © Springer Nature Switzerland AG 2021.